Papyrus : the invention of books in the ancient world - Vallejo Moreu, Irene (Alfred A. Knopf, 2022)
"Papyrus is an enthralling journey through the history of books and libraries in the ancient world and those who have helped preserve their rich literary traditions. Long before books were mass-produced, those made of reeds from along the Nile were worth fighting and dying for. Journeying along the battlefields of Alexander the Great, beneath the eruptions of Mount Vesuvius, at Cleopatra's palaces and the scene of Hypatia's murder, award-winning author Irene Vallejo chronicles the excitement of literary culture in the ancient world, and the heroic efforts that ensured this extraordinary tradition would continue. Weaved throughout are fascinating stories about the spies, scribes, illuminators, librarians, booksellers, authors, and statesmen whose rich and sometimes complicated engagement with the written word bears remarkable similarities to the world today: Aristophanes and the censorship of the humorists, Sappho and the empowerment of women's voices, Seneca and the problem of a post-truth world. Vallejo takes us to mountainous landscapes and the roaring sea, to the capitals where culture flourished and the furthest reaches where knowledge found refuge in chaotic times. In this sweeping tour of the history of books, the wonder of the ancient world comes alive and, along the way, we discover the singular power of the written word"--